Stand-alone mapping using different transluminal mapping catheters: an accurate and safe way to isolate all pulmonary veins with the cryoballoon? - Schade, Anja; Schumacher, Burghard (Journal of interventional cardiac electrophysiology, 2015)
Purpose: Cryoballoon isolation of the pulmonary veins (PVI) is an effective and safe method in the treatment of patients with paroxysmal atrial fibrillation (PAF). The circular mapping catheter Achieve (Medtronic Inc., Minneapolis, USA) can be introduced into the pulmonary vein (PV) through the inner lumen of the balloon catheter, allowing online mapping of the PV electrograms during ablation. We prospectively compared the accuracy of this catheter in both available sizes to a standard circular mapping catheter (SCMC) in order to determine bidirectional PV block. Methods: Patients with symptomatic PAF underwent cryoballoon ablation using either the Achieve 15-mm catheter (group 1, 15 patients) or the Achieve 20 mm (group 2, 15 patients). PV potentials were recorded using Achieve before, during, and after ablation, and exit block was obtained by pacing from inside the PV. Accuracy of PV potential detection was controlled by a SCMC before and after ablation. Results: Rate of PV which could be isolated exclusively using the Achieve as guidewire was 98 % (59/60) in group 1 and 93 % (57/60) in group 2. Online signal recording during ablation was possible in 40 and 60 % of PV (p = 0.037), respectively. Final Achieve diagnosis was accurate in 55/60 (92 %) of the PVs and 12/15 (80 %) of patients in group 1 and 60/60 (100 %) of PV and 15/15 (100 %) of patients in group 2. Conclusion: Stand-alone mapping using Achieve 15 mm resulted in a significant lack of diagnostic accuracy. Achieve 20 mm provided excellent diagnostic accuracy comparable to a SCMC and should be preferentially used.
Gesehen am 19.11.2018
Published online: 13 December 2014